Modelagem para distribuição de importâncias entre funcionalidades que compõem os pilares de manufacturing execution system em aplicações industriais - Vargas, Elisandro João de (Universidade do Vale do Rio dos Sinos, 2016)
Information systems have been progressively introduced in manufacturing environments. This is due to the need to capture data, optimize processes and generate information efficiently, including real-time production operations, to facilitate decision-making by managers and analysts. The Manufacturing Execution System (MES), called the Manufacturing Control System, can help companies capture data and generate information, identify and improve their results. However, simple access to an information system does not assure advantage. Therefore, to achieve consistent results, downstream and upstream alignment between strategies and tactics is required for production practices with the information systems available on the factory floor. In this sense, this research sought to answer the research problem how to determine the focus of the features that make up the core functions of a MES for the satisfaction of the strategic objectives of the manufacture; being the MES represented by the core functions and its features and manufacturing strategy represented by the competitive capabilities. The overall objective was to elaborate a model that can distribute importance between the features that make up the core functions of a MES for industrial applications. The research method used was qualitativequantitative modeling and the techniques of data collection were interviews, application of the Analytic Hierarchy Process (AHP) and Likert scale, and focus group. The developed model allows identifying a vector of importance between features and a quadrant between application and improvement of these vectors. Thereby, it allows companies that have or are look up to deploy MES systems and MES system applicators to identify which elements of manufacturing measurement and control most represent the strategic objectives of manufacturing; besides contributing to the advancement in research on MES and manufacturing strategy. This model was applied in two companies that date the use of the MES of eleven and eight years, with diferente product and processes. The results obtained were considered consistent and representative to the reality of the companies.
Keywords: Sistemas de informação; Manufacturing execution system; Pilares do MES; Funcionalidades do MES; Estratégia da manufatura; Prioridades de competência da manufatura; Information systems; Core functions of MES; Features of MES; Manufacturing strategy; Competitive capabilities; ACCNPQ::Engenharias::Engenharia de Produção